Efficacy of the DRL orthokeratology lens in slowing axial elongation in French children - Queirós, António; Rolland le Moal, Pauline; Angioi-Duprez, Karine; Berrod, Jean-Paul; Conart, Jean-Baptiste; Chaume, Aurélia; Pauné, Jaume (Frontiers in Medicine, 2024)
Background This study aims to assess and compare the impact of Orthokeratology Double Reservoir Lens (DRL) versus Single Vision Lenses (SVL) on axial elongation and anterior chamber biometric parameters in myopic children over a 6- and 12-month treatment period in France. Methods A retrospective study involving 48 patients aged 7 to 17 years, who underwent either orthokeratology treatment or single-vision spectacle correction, was conducted. Changes in refractive error, axial length, and anterior chamber depth were examined. Results Twenty-five patients comprised the Orthokeratology (OK) group, while twenty-three were in the control group (single-vision spectacle group). Significant increases in mean axial length were observed over time in both the control (0.12 ± 0.13 mm and 0.20 ± 0.17 mm after 6 and 12 months, respectively; F (2,28.9) = 27.68, p < 0.001) and OK groups (0.02 ± 0.07 mm and 0.06 ± 0.13 mm after 6 and 12 months, respectively; F (2,29.1) = 5.30, p = 0.023). No statistically significant differences in axial length were found between male and female children (p > 0.620). Age-specific analysis revealed no significant axial elongation after 12 months in the 14–17 years group in the OK group. Anterior biometric data analysis at 6 and 12 months showed statistical significance only for the DRL group. Conclusion Orthokeratology resulted in an 86 and 70% reduction in axial elongation after 6 and 12 months of lens wear, respectively, compared to the single-vision spectacles group. Myopia progression was more pronounced in younger children, underscoring the importance of initiating myopia control strategies at early ages.